EFFECTS OF COOPERATIVE LEARNING AND FIELD TRIP STRATEGIES ON JUNIOR SECONDARY SCHOOL STUDENTS’ KNOWLEDGE OF AND ATTITUDE TO MULTICULTURAL CONCEPTS IN SOCIAL STUDIES (2014)
The growing spate of ethno-religious crisis and insurgency that characterise the Nige-rian polity have been traced partially to inadequacies in the teaching of multicultural concepts in social studies. The teaching and learning of these concepts through cooperative learning and field trip strategies could discourage discrimination and promote mutual respect for other cultures. A number of studies had been carried out on cooperative learning and field trip strategies which confirmed their effectiveness on student achievement but majority of such studies had been limited to mathematics, geography, sciences and environmental education with little consideration for multicultural education. This study, therefore, determined the ef-fects of cooperative learning and field trip strategies on junior secondary school students‘ knowledge of and attitude to multicultural concepts in social studies. It further determined the moderating effects of ethnic origin and religion.The pretest-posttest, control group, quasi-experimental design with a 3x2x2 factorial matrix was adopted. Participants were three hundred and fifty-two junior secondary III stu-dents purposively selected from six secondary schools in Abeokuta, Ogun State. Participants were randomly assigned to cooperative learning strategy, field trip strategy and control groups; while treatment lasted ten weeks. Five instruments used were: Multicultural Concepts Knowledge Test (r=0.82), Multicultural Concept Attitude Scale (r= 0.86); Teachers‘ Instruc-tional Guide for Cooperative Learning Strategy, Teachers‘ Instructional Guide for Field Trip Strategy and Teachers Instructional Guide for the conventional method. Seven null hypothe-ses were tested at p<0.05 level of significance. Data were analysed using descriptive statis-tics, analysis of covariance and Scheffé post hoc test.Treatment had significant main effect on students‘ posttest knowledge scores in mul-ticultural concepts (F(2,340)=5.84; =.25) and attitude to multicultural concepts (F(2,340)=34.06; =0.40). Students in the cooperative learning group had higher mean knowledge score (x=10.14) than those in the field trip ( x =7.95) and the control group (x=10.09). Students in the control group obtained the highest adjusted posttest attitude score (x=82.26) while those in the cooperative learning group had x =79.05 and those in the field trip group had x =64.67. There was a significant interaction effect of treatment and ethnic origin on students‘ knowledge of multicultural concepts (F(2,340)=9.17; =0.32) while the coop-erative learning strategy benefited three hundred and ten students from Yoruba ethnic origin.The field trip strategy benefited forty-two non-Yoruba students. There was a significant main effect of treatment and religion on students‘ knowledge of multicultural concepts (F(2,340)=5.06; =0.13). The cooperative learning strategy benefited one hundred and nine-ty-eight students of Christian faith while the field trip strategy benefited one hundred and fif-ty-four students of Islamic faith.Cooperative learning and field trip strategies were both effective at enhancing stu-dents‘ knowledge of and attitude to multicultural concepts in social studies with ethnic fla-vour. Teachers should adopt both strategies to complement the conventional method for ef-fective teaching of multicultural concepts in social studies